Nonsmooth minimization problems for the difference of two convex functions - Gruzdeva, T.V.; Strekalovsky, A.S.; Orlov, A.V.; Druzinina, O.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
The global search theory in nonsmooth d.c. minimization problems (the goal function is represented as the difference of two convex functions) is generalized to the nondifferentiable case. Several algorithms of local and global search in problems with nonsmooth goal functions are proposed and their convergence is studied. The proposed algorithms are numerically tested.